2008
DOI: 10.1097/mpg.0b013e31815ce599
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Studies of Fecal Anaerobic Commensal Bacteria in Acute Diarrhea in Children

Abstract: Specific classes of fecal bacteria are lower during episodes of acute diarrhea in children than during periods of normal gastrointestinal health, suggesting specific alterations in the flora during diarrhea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 28 publications
3
38
1
1
Order By: Relevance
“…Similar results were also observed in some other studies (Ramakrishna et al, 2000;Balamurugan et al, 2008;Alam et al, 2009). Clinical recovery was associated with a striking increase in the concentrations of bacteria and SCFAs with time.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Similar results were also observed in some other studies (Ramakrishna et al, 2000;Balamurugan et al, 2008;Alam et al, 2009). Clinical recovery was associated with a striking increase in the concentrations of bacteria and SCFAs with time.…”
Section: Discussionsupporting
confidence: 78%
“…However, the basis for such a mechanism requires the presence of metabolically active bacteria in the colon. In malnutrition as well as in diarrhoea the number, biodiversity and function of the bacteria are altered (Ramakrishna et al, 2000;Balamurugan et al, 2008;Alam et al, 2009). In addition, antibiotics are often used in the initial phase of treatment of malnutrition and cholera (World Health Organization, 2009a, b).…”
Section: Introductionmentioning
confidence: 99%
“…26,27 While this finding was unexpected, a previous study of Indian children found that the abundance of Lactobacillus species increased at the end of diarrhea episodes and then decreased after 3 months of recovery. 28 Also, as compared with diarrhea stools, recovery stools had a greater relative abundance of genera of the order Clostridiales (Dorea, Blautia, Dialister, and Sporobacterium WAL_1855D). Some of these Clostridiales genera are known to produce the short-chain fatty acid, butyrate, which promotes the growth of the intestinal epithelium.…”
Section: Discussionmentioning
confidence: 96%
“…There is a depletion of the anaerobic flora which allows the overgrowth of Proteobacteria , particular enterococci [39]. This tendency is exacerbated by antibiotics, so it is perhaps no surprise that the patients who have received antibiotics for salmonellosis have more long-lasting IBS symptoms [40].…”
Section: Mechanism Of Postinfectious Ibsmentioning
confidence: 99%